Analisis Kesalahan Pelafalan Perubahan Tona “Bu” Bahasa Mandarin - Wikarti, Aprilia Ruby (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Abstract:In tonal languages such as Mandarin, tone is a suprasegmental phoneme that can distinguish meaning. A certain syllable can undergo a change in tone, depending on the syllable that comes after it. One of the changes in tone that often occurs is the change in tone bu, which means